QuantiFERON-TB Gold Test Conversion Is Associated with Active Tuberculosis Development in Inflammatory Bowel Disease Patients Treated with Biological Agents: An Experience of a Medical Center in Taiwan - Hsiang-Chun Lai; Chia-Hsi Chang; Ken-Sheng Cheng; Tsung-Wei Chen; Yuan-Yao Tsai; Jen-Wei Chou (Gastroenterology Research and Practice)
Taiwan has a lower prevalence of inflammatory bowel disease (IBD) and a higher prevalence of tuberculosis (TB) infection than Western countries. The aim of this study was to investigate the prevalence of latent TB (LTB) and active TB infection in IBD patients treated with biological agents. From January 2000 to September 2018, we retrospectively collected data from IBD patients treated with biological agents at a tertiary referral center. Patients underwent a QuantiFERON-TB Gold test (QFT) to screen for TB infection before and after biological treatment courses. The diagnostic age, sex, body mass index, hepatitis B virus infection, biochemistry profile, treatment regimens, and the results of the QFT were analyzed. Overall, 130 IBD patients who received biological treatment were enrolled. The results of the QFT before biological treatment were determined in 120 patients (92%); of these, 10 were positive (8%), 110 were negative (85%), and 10 were indeterminate (9%). Six patients demonstrated seroconversion after biological treatment, as determined by the QFT. Three patients (2.4%) developed active pulmonary TB after biological treatment. In subgroup analysis, the positive QFT patients had a trend of lower baseline serum C-reactive protein and erythrocyte sedimentation rate levels than the negative QFT group. The present study demonstrates that the prevalence of LTB before and after biological treatment is higher in Taiwan than in most Western countries and similar to other Asian countries. Therefore, screening and monitoring of TB infection are necessary for IBD patients before and during biological treatments in Taiwan.